Monocyte to high-density lipoprotein ratio as biomarker for cardiovascular health and cognitive function in the elderly diabetic and nondiabetic population: a case–control study - Christina S. Ragheb; Manal Roshdy El Masry; Mohamed Elbasel; Mai Galal; Ahmed Rabiee (The Egyptian Journal of Internal Medicine)
Abstract Background Atherosclerosis plays a crucial role in the progression of cardiovascular disease, which is still a major global health concern. Its onset and advancement are significantly influenced by inflammation, especially when it comes to the immune system’s relationship with hypercholesterolemia. Effective serum biomarkers for atherosclerosis are still elusive, despite continuous research into anti-inflammatory therapies. Both monocytes and high-density lipoprotein play important roles in inflammatory and antioxidant processes, while high-density lipoprotein cholesterol (HDL-C) provides protective benefits, and monocytes are involved in the development of atherosclerotic plaque. The monocyte to high-density lipoprotein ratio (MHR) has emerged as a promising predictor of cardiovascular events, potentially more sensitive than each one’s individual levels. Studies have investigated the relationship between MHR and cardiovascular events in a number of diseases, such as acute coronary syndrome and chronic kidney disease. This study investigates the associations between MHR, atherosclerosis, arteriosclerosis, and cognitive impairment in elderly Egyptian populations, exploring its potential as a diagnostic marker and its role in predicting cognitive decline in diabetic individuals. Comprehending this intricate correlation is essential for developing preventive measures and targeted interventions for preventing cardiovascular disease and cognitive deterioration in the geriatrics. Results The study included 100 participants, 50 with type 2 diabetes and 50 nondiabetic, with a mean age of 67 years. Significant negative correlations were found between MHR and the 3MS test (r: − 0.353, p = 0.012) and (r: − 0.170, p = 0.238) and between carotid femoral PWV and the 3MS test in diabetics and in nondiabetics (r: − 0.453, p = 0.001) in both groups, suggesting a potential link between MHR and cognitive impairment. Conclusion This study highlights the complex relationship between monocyte to HDL-C ratio (MHR), atherosclerosis, and cognitive function in the elderly. Positive correlations were found between MHR and carotid intima-media thickness and carotid femoral PWV, suggesting a role for MHR in atherosclerosis. Notably, a negative correlation between MHR and cognitive function in diabetic individuals suggests a potential link between MHR and cognitive decline.